Responsibilities of graduate student: the review of research student policies - Zainal Abiddin, Norhasni; West, Mel (Science Publications, 2007)
The researcher’s previous study had found that most research students did not fully used their graduate research student policy as point of reference. Objective was to review the contents of the research student policy and the benefits of having systematic policies for the supervision of research students. Total of 40 graduate research student policies had been studied from 40 well established universities in the United Kingdom. We focused on the responsibilities of research student which stated in the policies. The results from this research had found that all the universities reviewed had their own research student policies. However, not all of them had clearly spell-out their respective policies in the student handbook. In the mean time, some universities had established additional aspects or information and they were systematically as well as precisely presented. Hence, the additional information or detailed guidelines presented by these particular universities were considered very useful in establishing the research student policy for the benefits of the student, supervisor as well as the school.